Validation of the Croatian version of the Sense of Coherence 29-item scale in Croatian nurses - Smrekar, Martina (Zdravstveno varstvo, 2020)
Introduction: The aim of the study was to validate the Croatian version of the Sense of Coherence 29-item instrument (SOC-29) within a nursing population. Methods: The cross-sectional study was conducted between December 2017 and June 2018 at the University Hospital Centre Sisters of Mercy (UHCSM) in Zagreb, Croatia. A total of 711 nurses participated in this study. Internal consistency reliability was evaluated using Cronbach%s alpha coefficient (%), while the structure of the questionnaire was verified by exploratory factor analysis (EFA) (method of extraction: principal component analysis (PCA)) and confirmatory factor analysis (CFA). Results: The instrument demonstrated high internal consistency (%=0.885). PCA analysis has identified five factors that together account for 48% of the variance. However, the observed factors could not be interpreted. In the CFA, none of the models fitted well, although the fit of the three-factor model (CMIN/DF=4.786, CFI=0.767, RMSEA=0.073) was slightly better in comparison with the one-factor model (CMIN/DF=6.072, CFI=0.685, RMSEA=0.084). As the three-factor model in PCA has been shown to be uninterpretable, and all three factors were mutually positive and significantly correlated (correlation coefficients: 0.365-0.521), this indicated a single factor in the background. All items also showed saturation with the first factor (accounting for 25.7% of the variance). Conclusions: The Croatian version of the SOC-29 instrument successfully fulfilled the necessary psychometric criteria for being used on the population of Croatian nurses. The study proposes that potential users use the single-factor structure.
Keywords: medicina dela; medicinske sestre; nurses; občutek koherentnosti; occupational medicine; reliability; Sense of Coherence; SOC-29; SOC-29 instrument; validity; veljavnost; zanesljivost